Functional Alterations Involved in Increased Bleeding in Hereditary Hemorrhagic Telangiectasia Mouse Models - Egido-Turrión, Cristina; Rossi, Elisa; Ollauri-Ibáñez, Claudia; Pérez-García, María L.; Sevilla, María A.; Bastida, José María; González-Porras, José Ramón; Rodríguez-Barbero, Alicia; Bernabeu, Carmelo; Lopez-Novoa, José M.; Pericacho, Miguel (Frontiers in Medicine, 2022)
Hereditary Hemorrhagic Telangiectasia (HHT) is an autosomal-dominant genetic disorder involving defects in two predominant genes known as endoglin (ENG; HHT-1) and activin receptor-like kinase 1 (ACVRL1/ALK1; HHT-2). It is characterized by mucocutaneous telangiectases that, due to their fragility, frequently break causing recurrent epistaxis and gastrointestinal bleeding. Because of the severity of hemorrhages, the study of the hemostasis involved in these vascular ruptures is critical to find therapies for this disease. Our results demonstrate that HHT patients with high bleeding, as determined by a high Epistaxis Severity Score (ESS), do not have prolonged clotting times or alterations in clotting factors. Considering that coagulation is only one of the processes involved in hemostasis, the main objective of this study was to investigate the overall mechanisms of hemostasis in HHT-1 (Eng+/-) and HHT-2 (Alk1+/-) mouse models, which do not show HHT vascular phenotypes in the meaning of spontaneous bleeding. In Eng+/- mice, the results of in vivo and in vitro assays suggest deficient platelet-endothelium interactions that impair a robust and stable thrombus formation. Consequently, the thrombus could be torn off and dragged by the mechanical force exerted by the bloodstream, leading to the reappearance of hemorrhages. In Alk1+/- mice, an overactivation of the fibrinolysis system was observed. These results support the idea that endoglin and Alk1 haploinsufficiency leads to a common phenotype of impaired hemostasis, but through different mechanisms. This contribution opens new therapeutic approaches to HHT patients’ epistaxis.